Preparation method and application of calcite / copper oxide modified glassy carbon electrode

CN118090860BActive Publication Date: 2026-10-16JIANGSU UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410234537.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-01
Publication Date
2026-10-16
Estimated Expiration
2044-03-01

AI Technical Summary

Technical Problem

不同的检测技术都有一定的缺陷:分光光度法比较适合于检测微量离子浓度,但也存在有毒试剂的使用问题与仪器昂贵的缺点;离子色谱法检测精度较高,对痕量离子的检测也有较大优势,但仪器体积庞大,价格昂贵,且对操作人员有要求;原子吸收法具有较高的精确度,也适用于微量离子含量的测定过程中,但该方法对光源要求比较高,且对被测样品需要进行特殊处理,仪器设备也存在价格昂贵的缺点;总之,现阶段的检测技术存在能检测到的氯离子浓度最低检测线不够低,且检测费用较高,操作复杂等缺陷

Benefits of technology

[0031] 1. This application provides a method for detecting chloride ion concentrations with lower detection limits. The synthesis method is simple, low-cost, and can be used for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118090860B_ABST
    Figure CN118090860B_ABST
Patent Text Reader

Abstract

The embodiment of the application relates to a preparation method and application of a mayenite / copper oxide modified glassy carbon electrode, and belongs to the technical field of electrochemical analysis. The preparation method of the mayenite / copper oxide modified glassy carbon electrode comprises the following steps: S1, dissolving pseudo-boehmite powder and calcium hydroxide in water to generate katoite Ca3Al2(OH) 12 ) through reaction; S2, dissolving a copper source and an alkaline compound in water, washing, drying to obtain copper oxide CuO; S3, dissolving the katoite and the copper oxide in water, magnetically stirring, adding a glucose solution, centrifuging, washing after reaction completion, performing calcination treatment, grinding the calcined product and redispersing the calcined product in water to obtain a mayenite / copper oxide mixed solution; and S4, dropping the mayenite / copper oxide mixed solution on a glassy carbon electrode and dropping a naphthol solution, and obtaining the mayenite / copper oxide modified glassy carbon electrode after drying. The synthesis method is relatively simple, low in cost and capable of being used for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical analysis technology, and in particular to a method for preparing and applying a calcium aluminate / copper oxide modified glassy carbon electrode. Background Technology

[0002] Water is an indispensable element in the entire Earth's ecosystem and the most precious natural resource. Water quality is closely related to the ecological environment. While my country has abundant total water resources, its per capita share is extremely low, making the water resource situation worrying. Since the reform and opening up, continuous socio-economic development and accelerated industrialization and urbanization have led to a continuous increase in the demand for industrial, agricultural, and domestic water use. However, this development has been accompanied by serious water pollution problems, creating a stark contradiction with the limited water resources available. Water resource issues are now urgently needing to be addressed. Water resources are inextricably linked to economic growth and food security; they are not only a precious and scarce resource but also an essential strategic resource for national economic development and long-term stability. To address the current severe water resource situation, the monitoring and control of water quality parameters are indispensable, whether for the utilization of seawater and groundwater or the treatment of wastewater. Chloride ion concentration is a crucial indicator in water quality monitoring. Chloride ions, a common ion in the aquatic environment, are essential in disinfection, scalding, and many other production processes. As an easily polarized anion, polarization significantly accelerates corrosion reactions, and excessively high concentrations can cause considerable harm. High chloride ion concentrations in drinking water produce a strong odor and can harm human health; high chloride ion concentrations in swimming pool water can damage human skin; chloride ions in boiler steam corrode boiler pipes and turbine blades, affecting their service life; chloride ions in inland river water corrode bridges; chloride ions in reinforced concrete corrode steel bars, accelerating building aging; high chloride ion concentrations in soil water hinder plant growth and damage the ecological environment; and during disinfection, excessively low chloride ion concentrations are ineffective in killing pathogenic microorganisms, resulting in poor disinfection effects.

[0003] In conclusion, the accurate measurement of chloride ion concentration is of paramount importance, impacting human health and industrial safety. Therefore, detecting low concentrations of chloride ions is a pressing issue. Common methods for chloride ion detection include electron spin resonance, spectrophotometry, atomic absorption spectrometry, chemiluminescence, chromatography, fluorescence, and electrochemical methods. Relatively speaking, electrochemical instruments offer advantages in quantitative chloride ion analysis due to their fast reaction speed, high sensitivity, low cost, and ease of real-time monitoring. Different detection techniques each have their drawbacks: spectrophotometry is suitable for detecting trace ion concentrations, but it suffers from the use of toxic reagents and expensive equipment; ion chromatography offers high accuracy and has a significant advantage in detecting trace ions, but the equipment is bulky, expensive, and requires skilled operators; atomic absorption spectrometry has high precision and is also suitable for determining trace ion content, but this method requires a high-quality light source and special treatment of the sample, and the equipment is also expensive; in short, current detection techniques suffer from drawbacks such as insufficient minimum detection limits for chloride ion concentrations, high detection costs, and complex operation. Summary of the Invention

[0004] In view of this, this application provides a method for preparing and applying a calcium aluminum stone / copper oxide modified glassy carbon electrode, which can detect chloride ion concentrations with lower detection limits. The synthesis method of this application is relatively simple and inexpensive, and can be used for large-scale industrial production, effectively overcoming the defects of the prior art.

[0005] The first aspect of this application provides a method for preparing a calcium aluminate / copper oxide modified glassy carbon electrode, comprising the following steps:

[0006] S1. Preparation of Kato-stone: Pseudoboehmite powder and calcium hydroxide are dissolved in water, and the reaction produces Kato-stone Ca3Al2(OH). 12 ;

[0007] S2. Preparation of copper oxide: Copper source and alkaline compound are dissolved in water, washed and dried to obtain copper oxide CuO;

[0008] S3. Preparation of calcium aluminum stone / copper oxide composite material: Kato stone and copper oxide are dissolved in water, magnetically stirred, glucose solution is added, centrifuged and washed after the reaction is completed, calcined, the calcined product is ground and redispersed in water to obtain calcium aluminum stone / copper oxide mixture.

[0009] S4. Preparation of calcium aluminate / copper oxide modified glassy carbon electrode: A calcium aluminate / copper oxide mixture is drop-coated onto a glassy carbon electrode, followed by a naphthol solution. After drying, a calcium aluminate / copper oxide modified glassy carbon electrode is obtained.

[0010] In some embodiments that may include the above embodiments, in step S1, the mass ratio of pseudoboehmite powder to calcium hydroxide is 3:4; or

[0011] In step S2, the mass ratio of copper source to alkaline compound is 10:1.

[0012] In some embodiments that may include the above embodiments, the process of step S3 is as follows:

[0013] Take Kato stone Ca3Al2(OH) 12 Copper oxide was dissolved in water and magnetically stirred. During the stirring process, glucose solution was slowly added. After the reaction was completed, the mixture was centrifuged, washed, and calcined. The calcined product was ground, dissolved in water, and ultrasonically dispersed. After magnetic stirring, it was ultrasonicated again to obtain calcium aluminum oxide / copper oxide mixtures with different molar ratios.

[0014] In some embodiments that may include the above-described embodiments, the specific reaction conditions in step S3 are: after reacting at room temperature for 1 hour, continuing the reaction at a temperature of 70–80°C for 2 hours; or

[0015] The calcination temperature is 350℃, and the time is 3 hours; or

[0016] The molar ratio of Kato stone:copper oxide:glucose is (3-6):(3-9):1.

[0017] In some embodiments that may include the above embodiments, in step S4, the glassy carbon electrode is pretreated before the calcium aluminum stone / copper oxide mixture is drop-coated onto the glassy carbon electrode. The process is as follows: the glassy carbon electrode is first polished with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, then polished with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, and placed in a cool place to air dry naturally for later use.

[0018] The second aspect of this application also provides a calcium aluminate / copper oxide modified glassy carbon electrode prepared by the preparation method described above.

[0019] The third aspect of this application also provides the application of the calcium aluminate / copper oxide modified glassy carbon electrode as described above in the electrochemical detection of chloride ions.

[0020] In some embodiments that may include the above embodiments, the step of electrochemical detection of chloride ions includes:

[0021] (1) Prepare chloride ion aqueous solutions of different concentrations using PBS buffer solution;

[0022] (2) A three-electrode system was formed by using a calcium aluminum stone / copper oxide modified glassy carbon electrode as the working electrode, a platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. The three-electrode system was placed in an aqueous chloride ion solution.

[0023] (3) Differential pulse voltammetry was used to electrochemically detect chloride ions and obtain the peak currents corresponding to different concentrations of chloride ions.

[0024] (4) Plot a standard curve with peak current as the ordinate and concentration as the abscissa;

[0025] (5) Place the three-electrode system in an aqueous chloride solution of unknown depth to obtain the differential pulse voltammetry curve and peak current of the aqueous chloride solution of unknown concentration, and obtain the chloride concentration according to the standard curve.

[0026] In some embodiments that may include the above examples, the concentrations of the chloride ion aqueous solutions of different concentrations are respectively: 1×10 -9 mol / L, 1×10 -10 mol / L, 1×10 -11 mol / L, 1×10 -12 mol / L, 1×10 -13 mol / L, 1×10 - 14 mol / L; or

[0027] The electrochemical parameters for differential pulse voltammetry are: scan potential range of -0.8 to 0 V, and scan rate of -0.2 mV / s.

[0028] It should be noted that this application uses a negative scan. In cyclic voltammetry testing, the voltage window is generally set from negative to positive. Taking the standard electrochemical peaks as an example, the positive scan peaks are the peak potentials and peak currents when the reduced substance in the system undergoes electrochemical oxidation on the working electrode surface. The negative scan peaks are the peak potentials and peak currents when the oxidized substance in the system undergoes electrochemical reduction on the working electrode surface.

[0029] In some embodiments that may include the above examples, the detection limit for chloride ions by differential pulse voltammetry is 6 × 10⁻⁶. -15 mol / L, linear range is 2×10 -15 -6×10 -15 mol / L.

[0030] Compared with the prior art, the embodiments of this application have the following beneficial effects:

[0031] 1. This application provides a method for detecting chloride ion concentrations with lower detection limits. The synthesis method is simple, low-cost, and can be used for large-scale industrial production.

[0032] 2. This application enables the electrode to produce a more obvious detection value at lower chloride ion concentrations. Because the electrochemical sensor has good activity, sensitivity, selectivity, reproducibility and stability, the detection limit for detecting different ions is very low, and it is efficient, fast, easy to operate and can perform real-time detection, thus becoming the best choice. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 These are IV diagrams of the electrodes in Examples 1-3 and Comparative Examples 1-3 of this application;

[0035] Figure 2 These are IV diagrams of the electrodes in Examples 1 and 4-6 of this application at different drop coating amounts;

[0036] Figure 3 This is an IV diagram of the electrode in Example 1 of this application at different enrichment times;

[0037] Figure 4 This is a morphology diagram of the calcium aluminum stone / copper oxide composite in Example 1 of this application;

[0038] Figure 5 This is a standard curve diagram corresponding to the electrodes in Embodiment 1 of this application. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0040] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods; all reagents used are of analytical grade, and all experimental water is double-distilled water.

[0041] In the embodiments of this application, the analytical instruments are CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.), BT125D electronic analytical balance (Mettler-Toledo Instruments Ltd.), and PHS-2F pH meter (Leici-Shanghai Instrument & Electronics Scientific Instruments Co., Ltd.).

[0042] Example 1

[0043] A method for preparing a calcium aluminum stone / copper oxide modified glassy carbon electrode includes the following steps:

[0044] At room temperature, 18g of boehmite powder and 24g of calcium hydroxide were dissolved in 200mL of water, and the reaction produced Katoite Ca3Al2(OH). 12 10g of copper sulfate and 1g of sodium hydroxide were dissolved in water and reacted. After 5-10 minutes, the mixture was heated until it turned black. After filtration, it was washed three times with deionized water and finally dried at 85℃ to obtain copper oxide CuO.

[0045] Add 5g of Kato stone Ca3Al2(OH) 12 1.06 g of copper oxide was added to a beaker, along with 20 ml of deionized water. While stirring magnetically, 0.8 g of glucose solution (5% by mass) was slowly added. The mixture was reacted at room temperature for 1 hour to obtain the precursor solution. The reaction was then continued at 75°C for 2 hours. After the reaction was complete, the sample was centrifuged and washed three times. The washed solid component was calcined at 350°C for 3 hours. After the reaction, the mixture was allowed to cool naturally to room temperature, ground into powder, placed in a beaker, and 20 ml of ultrapure water was added. The mixture was sonicated for 1 hour, then stirred with a magnetic stirrer for 2 hours. Finally, the stirred solution was sonicated for another 3 hours to obtain CuO / Ca. 12 Al 14 O 33 The mixture, i.e., CuO / Ca with a molar ratio of 1:1 12 Al 14 O 33 Mixture;

[0046] The glassy carbon electrode was first polished with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, and then polished again with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, and placed in a cool place to air dry naturally for later use; a CuO / Ca molar ratio of 1:1 was prepared. 12 Al 14 O 33 After sonicating the mixture for 5 minutes, immediately transfer 10 μL to the prepared glassy carbon electrode using a pipette and let it air dry in a cool place. Then transfer 12 μL of naphthol to the glassy carbon electrode prepared in the previous step and let it air dry in a cool place again to obtain the modified electrode copper oxide / calcium aluminum stone.

[0047] Example 2

[0048] The preparation method in this embodiment is the same as in Example 1, except that a CuO / Ca molar ratio of 1:2 is prepared. 12 Al14 O 33 The mixture, corresponding to the amounts added, is 5g of Kato stone, 2.12g of copper oxide, and 0.8g of glucose.

[0049] Example 3

[0050] The preparation method in this embodiment is the same as in Example 1, except that a CuO / Ca molar ratio of 1:3 is prepared. 12 Al 14 O 33 The mixture, corresponding to the amounts added, is 5g of Kato stone, 3.18g of copper oxide, and 0.8g of glucose.

[0051] Example 4

[0052] The preparation method of this embodiment is the same as that in Embodiment 1, except that 8 μL is transferred to the prepared glassy carbon electrode using a pipette.

[0053] Example 5

[0054] The preparation method of this embodiment is the same as that in Example 1, except that 12 μL is transferred to the prepared glassy carbon electrode using a pipette.

[0055] Example 6

[0056] The preparation method of this embodiment is the same as that in Example 1, except that 14 μL is transferred to the prepared glassy carbon electrode using a pipette.

[0057] Example 7

[0058] PBS buffer solution was used to prepare solutions with concentrations of 1×10⁻⁶. -9 mol / L, 1×10 -10 mol / L, 1×10 -11 mol / L, 1×10 -12 mol / L, 1×10 -13 mol / L, 1×10 -14 A mol / L aqueous solution of chloride ions;

[0059] The calcium aluminum oxide / copper oxide modified glassy carbon electrode prepared in Example 1 was used as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode to form a three-electrode system. The three-electrode system was placed in an aqueous chloride ion solution.

[0060] Differential pulse voltammetry was used to electrochemically detect chloride ions. The scanning potential range was -0.8 to 0 V, and the scanning speed was -0.2 mV / s. Peak currents corresponding to different concentrations of chloride ions were obtained.

[0061] Plot a standard curve with peak current as the ordinate and concentration as the abscissa, as shown below. Figure 5 As shown; the detection limit is 6×10⁻⁶.-15 mol / L, linear range is 2×10 -15 -6×10 -15 mol / L.

[0062] The three-electrode system was placed in an aqueous chloride ion solution of unknown depth to obtain the differential pulse voltammetry curve and peak current of the aqueous chloride ion solution of unknown concentration. The concentration of chloride ions was then determined based on the standard curve.

[0063] Similarly, the concentration of chloride ions in Examples 2 and 3 was tested using the same method as described above, with the detection limit and linear range being 1×10⁻⁶. -11 mol / L, 1×10 -11 -5×10 -9 mol / L and 1×10 -8 mol / L, 1×10 -8 -3×10 -6 mol / L.

[0064] Comparative Example 1

[0065] The bismuth ferrite-modified glassy carbon electrode provided in this comparative example is similar to Example 1, except that it does not contain calcium aluminum stone.

[0066] Comparative Example 2

[0067] The carbon nitride modified glassy carbon electrode provided in this comparative example is similar to Example 1, except that it does not contain copper oxide.

[0068] Comparative Example 3

[0069] The glassy carbon provided in this comparative example is the same as that in Example 1, except that it does not contain carbon nitride and bismuth ferrite, i.e., it is bare glassy carbon.

[0070] Application examples

[0071] Depend on Figure 1 It can be seen that, comparing Examples 1-3 and Comparative Examples 1-3, the chloride ion concentration is 1×10⁻⁶. -9 At a concentration of mol / L, the electrode in Example 1 exhibits the largest pulse peak at an enrichment voltage of -0.2 V. Therefore, it can be determined that when CuO:Ca... 12 Al 14 O 33 The detection effect is best when the molar ratio is 1:1.

[0072] Depend on Figure 2 It can be seen that when comparing the drop volume of Examples 1 and Examples 4-6, the pulse peak of the enrichment voltage at the -0.2V position is the largest when the drop volume is 12ul. Therefore, it can be concluded that the detection effect is the best when the drop volume is 12ul.

[0073] Figure 3 The image shows the IV curves of the electrode at different enrichment times in Example 1 of this application. As can be seen from the figure, the enrichment times are 50s, 100s, 150s, 200s, 250s, 300s, 350s, and 400s. The pulse peak is the largest at the enrichment time of 400s. However, the pulse peak at the enrichment time of 400s is very close to that at the enrichment time of 350s. Therefore, 350s is selected as the optimal enrichment time, and the detection effect is the best when the enrichment time is 350s.

[0074] Figure 4 The figure shows the morphology of the calcium aluminum stone / copper oxide composite material in Example 1 of this application. As can be seen from the figure, the calcium aluminum stone / copper oxide composite material forms a block shape, and the material can be well adsorbed on it, exhibiting good electrochemical properties.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for preparing a calcium aluminum oxide / copper oxide modified glassy carbon electrode, characterized in that, Includes the following steps: S1. Preparation of Kato-stone: Boehmite powder and calcium hydroxide are dissolved in water, and the reaction produces Kato-stone (Ca3Al2(OH)2). 12 ; S2. Preparation of copper oxide: Copper source and alkaline compound are dissolved in water, washed and dried to obtain copper oxide CuO; S3. Preparation of calcium aluminum stone / copper oxide composite material: Kato stone and copper oxide are dissolved in water, magnetically stirred, glucose solution is added, centrifuged and washed after the reaction is completed, calcined, the calcined product is ground and redispersed in water to obtain calcium aluminum stone / copper oxide mixture. S4. Preparation of calcium aluminate / copper oxide modified glassy carbon electrode: A calcium aluminate / copper oxide mixture is drop-coated onto a glassy carbon electrode, followed by a naphthol solution. After drying, a calcium aluminate / copper oxide modified glassy carbon electrode is obtained.

2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of boehmite powder to calcium hydroxide is 3:4; or In step S2, the mass ratio of copper source to alkaline compound is 10:

1.

3. The preparation method according to claim 1, characterized in that, The process of step S3 is as follows: Take Kato stone Ca3Al2(OH) 12 Copper oxide was dissolved in water and magnetically stirred. During the stirring process, glucose solution was slowly added. After the reaction was completed, the mixture was centrifuged, washed, and calcined. The calcined product was ground, dissolved in water, and ultrasonically dispersed. After magnetic stirring, it was ultrasonicated again to obtain calcium aluminum oxide / copper oxide mixtures with different molar ratios.

4. The preparation method according to claim 3, characterized in that, In step S3, the specific reaction conditions are as follows: after reacting at room temperature for 1 hour, continue the reaction at 70–80°C for 2 hours; or The calcination temperature is 350℃, and the time is 3 hours; or The molar ratio of Kato stone:copper oxide:glucose is (3-6):(3-9):

1.

5. The preparation method according to claim 1, characterized in that, In step S4, the glassy carbon electrode is pretreated before the calcium aluminum stone / copper oxide mixture is drop-coated onto the glassy carbon electrode. The process is as follows: the glassy carbon electrode is first polished with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, then polished with Al2O3 powder with a particle size of 1.0 μm for 10 minutes, rinsed with distilled water, and placed in a cool place to air dry naturally for later use.

6. The calcium aluminum oxide / copper oxide modified glassy carbon electrode prepared by the preparation method according to any one of claims 1-5.

7. The application of the calcium aluminum stone / copper oxide modified glassy carbon electrode as described in claim 6 in the electrochemical detection of chloride ions.

8. The application according to claim 7, characterized in that, The steps for electrochemical detection of chloride ions include: (1) Prepare chloride ion aqueous solutions of different concentrations using PBS buffer solution; (2) A three-electrode system was formed by using a calcium aluminum stone / copper oxide modified glassy carbon electrode as the working electrode, a platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. The three-electrode system was placed in an aqueous chloride ion solution. (3) Differential pulse voltammetry was used to electrochemically detect chloride ions and obtain the peak currents corresponding to different concentrations of chloride ions. (4) Plot a standard curve with peak current as the ordinate and concentration as the abscissa; (5) Place the three-electrode system in an aqueous chloride solution of unknown depth to obtain the differential pulse voltammetry curve and peak current of the aqueous chloride solution of unknown concentration, and obtain the chloride concentration according to the standard curve.

9. The application according to claim 8, characterized in that, The concentrations of chloride ion aqueous solutions of different concentrations are: 1×10 -9 mol / L, 1×10 -10 mol / L, 1×10 -11 mol / L, 1×10 -12 mol / L, 1×10 -13 mol / L, 1×10 -14 mol / L; or the electrochemical parameters for differential pulse voltammetry are: scanning potential range of -0.8 to 0 V, and scanning rate of -0.2 mV / s.

10. The application according to claim 8, characterized in that, The detection limit for chloride ions by differential pulse voltammetry is 6 × 10⁻⁶. -15 mol / L, linear range is 2×10 -15 -6×10 -15 mol / L.

Citation Information

Patent Citations

  • Preparation method for copper oxide-graphene nano-complex modification electrode, and application of modification electrode in glucose detection

    CN102520035A

  • Copper oxide nonenzymatic glucose electrochemical sensor

    CN107991371A